Intuitionistic Fuzzy Jensen-Rényi Divergence: Applications to Multiple-Attribute Decision Making (Informatica, 2025)
Intuitionistic Fuzzy Jensen-Rényi Divergence: Applications to Multiple-Attribute Decision Making